COMPARISON OF AUDIO VISUAL AND GET A STAR METHOD ON STUDENTS’ LISTENING ABILITY - Rizal Arisman; Ainun Rahmah; Melwinda Elisa Rahmi (Premise: Journal of English Education and Applied Linguistics, 2018)
This research is carried out to find out the significant difference of Audio Visual and Get a Star method on listening ability at grade nine students of SMP Negeri 3 Baubau in school year or 2017/2018. It is used a quantitative approach with experimental method. The population is grade eight students at SMP Negeri 3 Baubau in school year of 2017/2018 which consisted of 231 student. The sample is taking using cluster sampling; that is class IX.A which has 22 students taught by Getting a Star method and class IX.I which has 21 students taught by Audio Visual method. Instrument used are pretest and posttest. Data are analyzed using descriptive and inferential statistics. Result of the research indicates that there is not any significant difference between the use of Gett a Star and Audio Visual method on students’ listening ability. Besides, mean score of students’ listening ability taught by Get a Star method is 79.54 and taught by Audio Visual method was 79.52, in which those mean scores indicate that the students at class IX.A and IX.I have good listening ability.